(untitled) (International Journal of Food and Nutritional Sciences, 2021)
India has a long history of overseas investment. Since 1950s Indian companies have been venturing out to widen its business horizon and effectively participate in international business. Market-seeking, resource-seeking and asset-seeking have been the main motives of this vibrant community. First four decades did not produce any dramatic results; total outflows remained quite meager. Restrictive regime during 1950s through early 1990s was a conscious decision of the Government to make the economy self-sufficient and establish the assertion of Indian business houses in a mixed economy. There has been a surge in outflows from 2003-2004 onwards following significant dismantling of foreign exchange restrictions on capital transfers for acquisition of foreign ventures by Indian firms. India’s share in total outward FDI of developing countries increased from below 0.5 percent in the early 1990s to nearly 6 percent during 2006– 2007 and increases to around 14 % in 2017-18. Some of the Indian firms have attained global recognition and are now among the strongest EMNEs. Thus, the study will provide in-depth knowledge about effect on Macroeconomic factors on outward FDI on Indian Economyin India to the researchers and academicians through this Paper.